Aprovechamiento forestal y su impacto sobre la diversidad florística del bosque seco en Santa Elena año 2016. Programa de reforestación - Palma Ponce, Richard Leonardo (2016)
The research was conducted in the dry forest of the Commune Las Balsas, in order to determine the type of logging performed by community members and the possible impact on the floristic diversity. In this perspective it was determined that in the last five years, has been deforested around 119 hectares of dry forest , basically destining especially agriculture corn crop farm irrigation. In that Comuna 84% of its population engaged in some form of logging. Of these, 7% of the fruit harvest Barbasco (Jacquinia sprucei Mez) existing in the forest and sold in the local market, for the shrimp sector in the area; while which is 18%, for the production of wood charcoal is selectively extracted. 75% combine these two types of use. Among the species most used for the manufacture of coal consist; Mesquite (Prosopis juliflora), Guasmo (Pithecellobiun) Guayacan (Tabebuia chrysantha), Cascol (Caesalpinia glabrata Kunth), Ebony (Ziziphus thyrsiflora Bentham), morocho (Chionanthus compactus), Fernan Sanchez (Triplaris cumingiana), chalu (Leucaena trichodes), Vainillo (Senna spectabilis), among the most important. Although the Ministry of Environment of Ecuador, expressly prohibits the use of fine wood to make as guayacan (Tabebuia sp) and ebony (Zizupus thyrsiflora) in Las Balsas also they use it to have a better commercial value. When analyzed floristic diversity were recorded in plots show 552 individuals of 39 species, grouped in 24 families. Diversity indices were 2.15 and 0.83 for Shannon Simpson, meaning in both cases a high diversity of species. The family Mimosaceae ranks first, with five species and registered an Importance Value Index is 36.69%; Jacquinia species sprucei Mez (Barbasco) with 30.03%. The Guayacán and Ebon used in the production of coal have values of 19.6 and 16.37 respectively.